2011
DOI: 10.1016/j.jhydrol.2010.10.037
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty assessment of climate change impacts on the hydrology of small prairie wetlands

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(53 citation statements)
references
References 40 publications
0
49
0
4
Order By: Relevance
“…While this has been done for North America (e.g. Radić and Clarke, 2011;Zhang et al, 2011), river basins originating in the European Alps (e.g. Huss, 2011;Farinotti et al, 2012), for river basins worldwide (e.g.…”
Section: A F Lutz Et Al: Climate Change Implications For Central Amentioning
confidence: 99%
“…While this has been done for North America (e.g. Radić and Clarke, 2011;Zhang et al, 2011), river basins originating in the European Alps (e.g. Huss, 2011;Farinotti et al, 2012), for river basins worldwide (e.g.…”
Section: A F Lutz Et Al: Climate Change Implications For Central Amentioning
confidence: 99%
“…Daily maximum and minimum temperatures, solar radiation and relative humidity are then generated based on the presence or absence of rain for the day [40]. WXGEN stochastic weather generator is widely used for climate change studies [11,41,42].…”
Section: Scenarios Of Temperature Rainfall and Co2 Concentration Chamentioning
confidence: 99%
“…In particular, Gassman et al (2007) in their comprehensive review of SWAT model applications reported 22 peer-reviewed papers devoted to climate change impact assessment using SWAT (this number has undoubtedly grown since then; e.g. Kingston and Taylor 2010, Parajuli 2010, Zhang et al 2011, including related models, such as SWIM (Krysanova et al 1998). These assessments are typically done for small (49.6 km 2 ; Zhang et al 2011), medium (2098 km 2 ; Kingston and Taylor 2010) and large catchments (13 000-147 423 km 2 ; Huang et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Kingston and Taylor 2010, Parajuli 2010, Zhang et al 2011, including related models, such as SWIM (Krysanova et al 1998). These assessments are typically done for small (49.6 km 2 ; Zhang et al 2011), medium (2098 km 2 ; Kingston and Taylor 2010) and large catchments (13 000-147 423 km 2 ; Huang et al 2010). For water resources management, climate change impact assessments made at the medium and large scale are the most desired.…”
Section: Introductionmentioning
confidence: 99%